Dark passengers★ in stellar surveys. Issue 1 (24th August 2018) - Yalinewich, Almog; Beniamini, Paz; Hotokezaka, Kenta; Zhu, Wei
ABSTRACT: We develop stellar population models to predict the number of binaries with a single luminous member is Gaia and Hipparcos . Our models yield dozens of detections of black hole luminous companion (BHLC) binaries and hundreds to thousands of neutron star luminous companion (NSLC) binaries with Gaia . Interestingly, our models also yield a single detection of BHLC binary with Hipparcos, and a few NSLC binaries. We also show how the statistical distribution of detected binaries with a single luminous companion can be used to constrain the formation process of neutron stars and black holes.